IMPLEMENTATION MODEL PARENTING TO INCREASE THE INDEPENDENCE OF CHILDREN - Sunarty, Kustiah (Program Pascasarjana Universitas Negeri Makassar, 2015)
Â ABSTRACTThis study examines the implementation of the Model Parenting to increasethe Independence of children (PAO-MKA) in junior Makassar. PAO-MKA models developed by Sunarty (2014), and has tested the validity of experts and practitioners/teachers Counseling, and the results are valid, and ready implemented. The research problem is whether the Model PAO-MKA effectively increase the childs independence. The research objective was to determine the effectiveness of the Model PAO-MKA in an effort to increase the childs independence. This study uses a quantitative approach, with a type of pre-experimental study, models one group pretest-posttes design. Experiments conducted at SMPN 8 Makassar. Research subjects are divided into two groups, ie groups of children and parents, respectively numbered 30 people. Subjects the child is required in relation to the measurement of the childs independence. While the subject of the parents is required in relation to the implementation of the Model PAO-MKA. Data were analyzed by inferential statistics, the t test or the mean difference test. The results showed that there is a positive and significant difference between the level of the childs independence before (pretest) and after (posttest) training and implementation model of PAO-MKA. With the difference that the Model PAO-MKA declared effective increase the childs independence.Â Keywords: independence, parenting, PAO-MKA models.Â